FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IMPULSE BUYING GENERASI Z DI BANDAR LAMPUNG - Tami, Cintia Widuri; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
The Tiktok platform has a big impact on impulse buying among generation Z. This is the basis for how hedonic shopping motivation, electronic word of mouth and content marketing impact impulse buying among generation Z. This research aims to examine the influence of hedonic shopping motivation, electronic word of mouth and content marketing on impulse buying of generation z users of the tiktok platform in bandar Lampung. The method used in this research is explanatory research with a quantitative approach. The population determined to conduct this research is generation z users of the TikTok platform in Bandar Lampung with a research sample of 97 respondents collected through questionnaires distributed online. The sampling technique used to carry out samples in this research is a non-probability sampling technique with a type of purposive sampling or judgmental sampling. The analysis used to test the data in this research is multiple linear analysis. Based on the results of research and data analysis, it shows that hedonic shopping motivation has a partially significant effect on impulse buying by 95.5%. Then electronic word of mouth has a partially significant effect on impulse buying by 23.7% and content marketing has a partially significant effect on impulse buying by 39.9%. Based on the results of simultaneous tests, it shows that there is a significant influence between hedonic shopping motivation, electronic word of mouth, content marketing and impulse buying which simultaneously have a significant influence on impulse buying by 74.3%, while the remaining 25.7% is explained by other variables. which was not studied by researchers.